A pesca do budião-azul (Scarus trispinosus Valenciennes, 1840) no maior complexo coralíneo do Atlântico Sul. - Previero, Marília (2014)
Worldwide fishing of herbivorous fish has hampered the survival of many species of coral, unbalancing the competition between these, macroalgae and pathogens. The blue-dark parrotfish (Scarus trispinosus, Scaridae) is a large herbivorous fish that lives on reefs in the Brazilian coast. This fish plays a key role in the protection and survival of corals, and, however, in recent decades has been caught in increasing intensities on Abrolhos Bank, Bahia state, due to the reduction in other species. Here it was surveyed characteristics of S. trispinosus fishery, as well as quantitative information of fish landings. The paper was divided into two chapters. The first consisted of an investigation of historical and current characteristics of blue-dark parrotfish fishing, based on records of landings (obtained by fisheries monitoring between 2010 and 2011), length measurements of landed specimens and interviews with fishermen. The second chapter does a quantitative fishery investigation of S. trispinosus and evaluates the volume of landings, the Catch Per Unit Effort (CPUE), the abundance of S. trispinosus, the monthly variation in the lengths of captured specimens, the age structure of population, natural, total and fishing mortality, the survivorship and the magnitude of the effects of fishing on the population, considering the biology of the species and characteristics of the intensity of their catch. In the Abrolhos Bank the greenback parrotfish fishing occurs over 40 years and was intensified in the last 20 years with the new markets, with marketing the parrotfish fillet, and with reducing other target species. In Alcobaça port, larger specimens are landed, caught by diving with harpoon, in distant fishing sites. In the ports of Caravelas, of Marine Extractive Reserve of Corumbau and of Prado, smaller specimens are landed, caught by diving with harpoon and nets, in fishing shallow and near shore. The total catch of parrotfish fillet, recorded by fisheries monitoring in Caravelas was 24,80 t (on average 1,90 t per month), in the RESEX it was 1,93 t (on average 0,27 t per month), and in Alcobaça it was 9,21 t (on average 1,31 t per month). The CPUE in Caravelas ranged from 0.911 to 1.92 kgfisherman-1hour-1day-1, and in RESEX it ranged from 0.65 to 1.25 kgfisherman-1hour-1day-1. The biomass of greenback parrotfish between the sampling points reveals decline between the years 2002 and 2008, and an increase in 2009. Most captured individuals have between 8 and 9 years. The overall mortality rate was 0.87, natural mortality was 0.19, fishing mortality was 0.68 and survival was 0.42. Using the productivity and susceptibility evaluation (PSA), this species is intensively exploited by fishing in the Abrolhos Bank, with a score lower than 60. The lack of long term records of catches of this species hampers traditional assessments of the state of exploitation of this stock. It is expected that this study may contribute to the elaboration of proposals for effective fisheries management for the conservation of S. trispinosus without harming the fishing communities that depend on fishing to survive.